MAMPUKAH UKURAN PERUSAHAAN MEMODERASI PROFITABILITAS DAN LEVERAGE TERHADAP PENGHINDARAN PAJAK? - Rahmaningrum, Dewi; Syahzuni, Barlia Annis (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2025)
This study employs firm size as a moderating variable to examine and evaluate the impact of profitability and leverage on tax avoidance activities. The research focuses on companies in the raw materials manufacturing sector listed on the Indonesia Stock Exchange (IDX) during the period of 2021–2023. The authors utilized secondary data with purposive sampling techniques, resulting in a sample of 39 companies. Analysis was performed using statistical methods with Moderated Regression Analysis (MRA) and processed through statistical data analysis software. The findings reveal that while leverage does not impact tax avoidance, profitability does. Additionally, company size can moderate the impact of profitability on tax avoidance, but it is unable to moderate the impact of leverage on tax avoidance. These findings suggest that company management should prioritize having a compliant attitude towards its tax payments and not engage in tax avoidance as it relates to reputational risks and legal sanctions that may arise. Although leverage is not significant, capital structure management remains important for long-term business sustainability.